The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s12288-018-0920-6
|View full text |Cite
|
Sign up to set email alerts
|

Double Dose Plateletpheresis: A Savior to Shrinking Donor Pool and Platelet Inventory Management

Abstract: The double dose plateletpheresis (DDP) is considered to be a cost effective way of preparing platelets, owing to the low incidence of infectious complications and by also minimizing allogeneic donor exposure to the patients. We aimed at collecting DDP at our center and study its effect on donor hematological parameters, evaluate the product quality and the adverse donor reactions thereafter. Double Dose Platelet was collected from 160 eligible apheresis donors on Amicus cell separator (Fenwal, Inc. Three Corpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The collection efficiency observed in our study was 71.93 ± 25.14% in the control group and 72.07 ± 16.28% in the study group. Makroo et al 12 reported the CE to be 78.09%, while the CE observed by Chaudhary et al 24 was 59.7% and, in the study by Jaipian et al, 23 85.31%, for DDP collection using the Amicus. In a study conducted on the Trima Accel cell separator, the authors reported efficient DDP collection with a median PLT yield of 3.7 × 10 11 , mean CE of 74.99 ± 14.40% and mean CR of 0.096 ± 0.012 × 10 11 /min.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The collection efficiency observed in our study was 71.93 ± 25.14% in the control group and 72.07 ± 16.28% in the study group. Makroo et al 12 reported the CE to be 78.09%, while the CE observed by Chaudhary et al 24 was 59.7% and, in the study by Jaipian et al, 23 85.31%, for DDP collection using the Amicus. In a study conducted on the Trima Accel cell separator, the authors reported efficient DDP collection with a median PLT yield of 3.7 × 10 11 , mean CE of 74.99 ± 14.40% and mean CR of 0.096 ± 0.012 × 10 11 /min.…”
Section: Discussionmentioning
confidence: 88%
“… 27 Authors from India have also demonstrated the direct relationship between the pre-donation platelet count and platelet yield. 12 , 19 They also suggested that, in the Indian scenario, it would be more relevant to follow the European guidelines of a platelet yield > 2 × 10 11 platelets per unit. 19 …”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the continuous advancement of blood collection technology and equipment, the clinical demand has increased signi cantly every year. The plateletpheresis is a type of platelet collected by a blood cell separator that separates platelets and returns others to donors, have been shown to be relatively safe [9,10] . The plateletpheresis, which is obtained from a single donor and reduce the risk of transfusion reactions and disease transmission after blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…11 Several attempts have been made to predict whether a double platelet product could be obtained from a donor, which could help to optimize the available resources in developing countries. 12,13 This study aimed to assess the correlation of the predictive algorithms of the Trima Accel v. 6 (Terumo BCT) automated blood collection system with the quality control of the PCs and the blood cell count of the donor after the apheresis.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithms of several instruments, such as the Amicus Crescendo (Baxter Biotech Corp.), the MCS Plus Version LDL (Haemonetics Corp.), and the Trima Accel v. 5.0 (Gambro BCT) have been evaluated, however, a comprehensive assessment is still lacking, because this report only analyzes the mean of the differences between the prediction and the actual values 11 . Several attempts have been made to predict whether a double platelet product could be obtained from a donor, which could help to optimize the available resources in developing countries 12,13 . This study aimed to assess the correlation of the predictive algorithms of the Trima Accel v. 6 (Terumo BCT) automated blood collection system with the quality control of the PCs and the blood cell count of the donor after the apheresis.…”
Section: Introductionmentioning
confidence: 99%